JURNAL AKUNTANSI & INVESTASI : Analisis terhadap Dugaan Pemanfaatan Belanja Hibah, Belanja Bantuan Sosial dan Belanja Bantuan Keuangan Oleh Incumbent dalam Pemilukada Serta Efektivitasnya terhadap P - Citra Rizki Amalia, Suryo Pratolo (Akuntansi FE UMY, 2013)
The purpose of this research to proves whether there is the use of grant spending, social assistance spending and financial assistance spending by incumbent in Local General Election. This research is also to test effectiveness enhancement of grant spending, social assistance spending and financial assistance spending through the influence the three spending sources to local income enhancement in region of incumbent that conducted Local General Election 2011. The population of this research are both the province and regencies that conduct Local General Election 2011 with observation period 2009 until 2011. After purposived sampling, the result were get 62 region that conducted Local General Election consists of 37 region of incumbent area and 25 region of nonincumbent. The result of the analysis using SPSS shows that there is enhancement of grant spending, social assistance spending and financial assistance spending between before Local General Election and at the time of Local General Election in the region of incumbent in 2011. The results of the research that shows the enhancement proves that there is possibility of the use the three sources of spending in the Local General Election by incumbent for his political interest.